P300 and cAMP response element‐binding protein‐binding protein in skeletal muscle homeostasis, contractile function, and survival. Issue 2 (3rd January 2020) - Svensson, Kristoffer; LaBarge, Samuel A.; Sathe, Abha; Martins, Vitor F.; Tahvilian, Shahriar; Cunliffe, Jennifer M.; Sasik, Roman; Mahata, Sushil K.; Meyer, Gretchen A.; Philp, Andrew; David, Larry L.; Ward, Samuel R.; et al.
Abstract: Background: Reversible ε‐amino acetylation of lysine residues regulates transcription as well as metabolic flux; however, roles for specific lysine acetyltransferases in skeletal muscle physiology and function are unknown. In this study, we investigated the role of the related acetyltransferases p300 and cAMP response element‐binding protein‐binding protein (CBP) in skeletal muscle transcriptional homeostasis and physiology in adult mice. Methods: Mice with skeletal muscle‐specific and inducible knockout of p300 and CBP (PCKO) were generated by crossing mice with a tamoxifen‐inducible Cre recombinase expressed under the human α‐skeletal actin promoter with mice having LoxP sites flanking exon 9 of the Ep300 and Crebbp genes. Knockout of PCKO was induced at 13–15 weeks of age via oral gavage of tamoxifen for 5 days to both PCKO and littermate control [wildtype (WT)] mice. Body composition, food intake, and muscle function were assessed on day 0 (D0) through 5 (D5). Microarray and tandem mass tag mass spectrometry analyses were performed to assess global RNA and protein levels in skeletal muscle of PCKO and WT mice. Results: At D5 after initiating tamoxifen treatment, there was a reduction in body weight (−15%), food intake (−78%), stride length (−46%), and grip strength (−45%) in PCKO compared with WT mice. Additionally, ex vivo contractile function [tetanic tension (kPa)] was severely impaired in PCKO vs. WT mice at D3 ( 70–80% lower) and D5 ( 80–95% lower) and resulted in lethality within 1 week—a phenotype that is reversed by the presence of a single allele of either p300 or CBP. The impaired muscle function in PCKO mice was paralleled by substantial transcriptional alterations (3310 genes; false discovery rate < 0.1), especially in gene networks central to muscle contraction and structural integrity. This transcriptional uncoupling was accompanied by changes in protein expression patterns indicative of impaired muscle function, albeit to a smaller magnitude (446 proteins; fold‐change > 1.25; false discovery rate < 0.1). Conclusions: These data reveal that p300 and CBP are required for the control and maintenance of contractile function and transcriptional homeostasis in skeletal muscle and, ultimately, organism survival. By extension, modulating p300/CBP function may hold promise for the treatment of disorders characterized by impaired contractile function in humans.